DAYA HAMBAT EKSTRAK DAUN PEGAGAN (Centella asiatica) TERHADAP BAKTERI (Vibrio harveyii) SECARA IN VITRO - Zainuddin Zainuddin (Jurnal Teknologi Pangan dan Industri Perkebunan (LIPIDA), 2022)
Vibriosis disease is caused by Vibrio harveyii becteria attact. Use of antibiotics is prohibited because it has a negative impact on shrimp larvae because it will leave the residue in the body and cause resistence to V.harveyii. pegagan leaf (Centella asiatica) contains antibacterial active substances that can inhibit the growth of V.harveyii bacteria In Vitro. The purpose of this study is to determine the effectiveness of leaf extract of C.asiatica can inhibit thegrowth of V.harveyii bacteria In Vitro. The antibacterial test was performed by disc diffusion method, which consisted of 5 treatments, 5% 8% and 10% and 2 control, is positive control (Tetracycline 0,01%) and negative control (aquades). The result of secondary metabolite compound of C.asiatica extract was analyzedqualitively. In leaf extract of gotu kola contains bioactive compounds such as alkaloids, phenols, saponins and tannins. In the antibacterial test of C.asiatica extract was able to inhibit the growth of bacteria with the average diameter of inhibit zone formed from each concentration of extract that is 5% = 14,16 mm concentration 8% = 16,63 mm concentration 10% = 21,44. From the result, obtained leaf extract of C.asiatica showed the abilityto inhibit the growth of V.harveyii bacteria close to the drag in the positive control (tetracycline).